2011
DOI: 10.1186/1742-4690-8-98
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 infection by TNPO3 depletion is determined by capsid and detectable after viral cDNA enters the nucleus

Abstract: BackgroundHIV-1 infects non-dividing cells. This implies that the virus traverses the nuclear pore before it integrates into chromosomal DNA. Recent studies demonstrated that TNPO3 is required for full infectivity of HIV-1. The fact that TNPO3 is a karyopherin suggests that it acts by directly promoting nuclear entry of HIV-1. Some studies support this hypothesis, while others have failed to do so. Additionally, some studies suggest that TNPO3 acts via HIV-1 Integrase (IN), and others indicate that it acts via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
139
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 60 publications
11
139
1
Order By: Relevance
“…The decrease in WT A3F-YFP particles upon Nup153 knockdown was similar to the decrease in 2-LTR circles (1.7-vs. 2.3-fold decrease, respectively). There was no decrease in the number of nuclear A3F-YFP particles upon TNPO3 depletion in cells infected with WT or D110E virus, consistent with reports indicating that TNPO3 depletion acts on HIV-1 at a step after entry of the PIC into the nucleus (12,15,17,18). The decrease in 2-LTR circles (2.7-fold decrease) upon TNPO3 depletion, but not nuclear import of A3F-YFP particles, indicates that TNPO3 may affect the formation and/or stability of 2-LTR circles, which is consistent with a previous report (15).…”
Section: Significancesupporting
confidence: 76%
“…The decrease in WT A3F-YFP particles upon Nup153 knockdown was similar to the decrease in 2-LTR circles (1.7-vs. 2.3-fold decrease, respectively). There was no decrease in the number of nuclear A3F-YFP particles upon TNPO3 depletion in cells infected with WT or D110E virus, consistent with reports indicating that TNPO3 depletion acts on HIV-1 at a step after entry of the PIC into the nucleus (12,15,17,18). The decrease in 2-LTR circles (2.7-fold decrease) upon TNPO3 depletion, but not nuclear import of A3F-YFP particles, indicates that TNPO3 may affect the formation and/or stability of 2-LTR circles, which is consistent with a previous report (15).…”
Section: Significancesupporting
confidence: 76%
“…However, previous reports differ in implicating either HIV-1 IN or CA as direct binding partners of TNPO3 (12,19,22,23). Because these studies examined the interactions employing different experimental approaches, we compared TNPO3 interactions with HIV-1 IN and CA in parallel experiments using purified recombinant proteins and pulldown assays.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that the TNPO3 within the nucleus could be important for promoting HIV-1 integration (22)(23)(24). A mechanism was proposed whereby some PICassociated HIV-1 CA enters the nucleus and TNPO3 strips the CA from PICs to promote effective integration (24).…”
Section: Tnpo3 Does Not Interact Directly With Ca Tubes In Vitro-mentioning
confidence: 99%
See 1 more Smart Citation
“…protein (30)(31)(32)(33). A surprising discovery that a CPSF6 deletion mutant lacking the RS domain can potently inhibit HIV-1 replication through direct binding to capsid provides for a link between Tnpo3 and a viral component (34,35).…”
mentioning
confidence: 99%